The Effect of Annealing on The Structural and Optical Properties of SnS Thin Films - D.A. Mfarej, Hind; R. M.Al-Sarraf, Abdul Hameed; Al Anssari, Ramiz A. Mohammd; F. Habubi, Nadir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin  films   of  pure   tin mono-sulfide  SnS with thicknesses of   (0.85) Î¼m  were prepared by chemical spray  pyrolysis  technique  and  annealed for  two  hours with 673K.The effect of annealing on structural and optical properties for films prepared was  studied.  X-Ray   diffraction  analysis  showed   the  polycrystalline  with   orthorhombic structure.  It was  found  that   annealing process increased the intensity of diffraction peaks. Optical   properties  of  all  samples  were studied by  recording  the  absorption  and  transmission  spectrum in the  range   of   wave   lengths  (300-900) nm.  The  optical energy   gap   for direct    forbidden  transition    and   indirect   allowed transition   were evaluated